Pemakaian sorgum (Sorghum bicolor l.) sebagai bahan substitusi jagung (Zea mays l.) pada ransum terhadap berat bagian bagian karkas ayam broiler umur 6 minggu - Sosiawan Bulu; I Gusti Ayu Seri Rejeki; Ni Ketut Mardewi (GEMA AGRO, 2018)
Sorghum (Sorghum bicolor L.) is one alternative as a substitute for corn in rations, it is known that the nutrient content of sorghum is not much different from the nutrition of corn. The purpose of this study was to determine the effect of sorghum use as a substitute for corn in the ration on the weight of the carcass part and what percentage of sorghum substitution level had an effect on the weight of the carcass parts. This study used a completely randomized design (CRD) with 5 treatments and 3 replications. In each replication using 3 CP 707 broiler chickens aged 2 weeks with homogeneous body weight. The treatment is R0 (control ration without sorghum use), R1 (ration + 7% use of sorghum), R2 (ration + 14% use of sorghum), R3 (ration + 21% use of sorghum), R4 (ration + 28% use of sorghum). Variables observed were weight of the chest, weight of the wing, weight of the thigh, weight of the back. The results showed that the use of sorghum (Sorghum bicolor L.) as a substitute for corn at all levels had no significant effect on all parts of the carcass of broiler aged six weeks and the level of use of 21% sorghum tended to increase the weight of the carcass parts.